Konstruksi Belajar Multi Arah pada Implementasi Model Merdeka Belajar dan Kampus Merdeka (Learning Analysis of How to Learn based on Self Awareness) - Saiful Hadi (IAIN Madura, 2021)
Construction of multi direction which initiates students’ involvement by self-directed, collaborative, and institutional as learning approach, oriented on the effort of improving graduates capacity in which be able to apply their own knowledge and practical skill experience in working world that take advantage of wide learning source with learning model of research or inquiry through merdeka belajar dan kampus merdeka model, based on institution characteristics that its curriculum ignites the pattern of multi direction learning. Therefore, the students can analyze learning how to learn based on their learning needs. Implementation of multi direction strategy needs curriculum design of college that is adaptive suitable with the demands of contemporary regulation change and future needs which states in design of kurikulum kualifikasi nasional Indonesia (KKNI). The impact of construction multi direction implementation is employment skill and enterpreneurship based on community character values which are available in society life civilization. Employment skill dan entrepreneurship contain critical thinking element which grows students that have self capacity appearing in themselves that are able to think critically, think creatively, communicate effectively with other people and collaborate with colleague or tim work.